Short-segment posterior fixation with index level screws versus long-segment posterior fixation for thoracolumbar spine fracture: angle of correction and pain - Ahmed M. Sallam; Walid A. Abdel Ghany; Ali Kotb Ali; Mohamed A. Habib; Ahmed F. Toubar; Mohamed S. Kabil; Ahmed Abdel Barr Salem; Sherif H. Abouzeid Mourad; Mohamed A. Nada (Egyptian Journal of Neurosurgery, 2018)
Abstract Background Thoracic and lumbar fractures represent nearly 90% of traumatic spine injuries. Thoracolumbar region is susceptible to injury because of its location between the stiff kyphotic thoracic spine and the mobile lordotic lumbar region. To compare between short-segment fixation with screws into index level and long-segment fixation in maintaining angle of correction and pain. Methods A prospective study included 91 patients, who had single-level thoracolumbar fracture with Cobb’s angle ≤ 25° and underwent posterior fixation. Forty-four patients underwent short-segment fixation with screws into the index level, and 47 patients underwent long-segment fixation with skipped index level. The angle of correction, pain, and neurological state were regularly assessed. Results Forty-four patients (48.35%) had short segment and 47 (51.65%) had long-segment fixation. In the short segment group, the pre-operative mean Cobb’s angle was 19.34° ± 3.63° and the angle of correction was 8.14° ± 1.9° after 1 year, while in the long segment group, the pre-operative mean Cobb’s angle was 19.08° ± 4.0° and the angle of correction was 8.62° ± 2.59°. Regarding pain, in the short segment group, the pre-operative visual analogue scale (VAS) was 5.59 ± 2.09 that was reduced to 1.39 ± 0.58 at the 1 year follow-up, while the long segment group VAS was 5.4 ± 2.01 pre-operatively that was reduced to 1.47 ± 0.58. Conclusions Short-segment fixation can maintain the angle of correction as long-segment fixation for single level thoracolumbar traumatic fracture with lower complication and faster pain relief. Trial registration Clinicaltrials.gov/NCT03272243. Registered: 1 September 2017.